Assessing the in situ bacterial diversity and composition at anthropogenically active sites using the environmental DNA (eDNA). (September 2021) - Garlapati, Deviram; Kumar, B. Charan; Muthukumar, C.; Madeswaran, P.; Ramu, K.; Murthy, M.V. Ramana
Abstract: In this study, we identified the in situ bacterial groups and their community structure in coastal waters influenced by anthropogenic inputs. The use of environmental DNA (eDNA) and high throughput sequencing (HTS) were employed to derive accurate and reliable information on bacterial abundance. The V3 and V4 hypervariable regions of the 16S rRNA gene were amplified and the sequences were clustered into operational taxonomic units to analyze the site-specific variations in community composition. The percentage composition within the bacterial orders varied significantly among nearshore anthropogenic hotspots and offshore (5 km) samples. The microbial network constructed taking the bacterial abundance as nodes displayed strong positive and negative correlations within the bacterial families. Overall, the use of eDNA coupled with HTS is an incredible means for monitoring and assessing the abundance of bacterial communities and also serves as a biomonitoring tool to understand the degree of anthropogenic contamination in coastal waters. Graphical abstract: Unlabelled Image Highlights: Data on the most dominant marine bacteria and their community composition Data on the abundance of bacterial orders present in the anthropogenic hotspots along nearshore Application of recent molecular approach environmental DNA (eDNA) for sample collection Comparative study to derive an understanding on the in situ bacterial communities nearshore and offshore (5 km) waters